Martin Luther King and the American Legal System - Florianová, Eva (2007)
The thesis focuses on some legal aspects of Martin Luther King's activities during the civil rights movement. It includes the description of American legal system as well as legislation which was in force prior to 1954. It enlists the most important protests King took part in and reflects King's relationship to both the state and the federal courts